2023
DOI: 10.3390/su152014986
|View full text |Cite
|
Sign up to set email alerts
|

Utilization of Multilayered Polyethylene Terephthalate (PET)-Based Film Packaging Waste Using Reactive Compatibilizers and Impact Modifier

Piotr Szymczak,
Damian Dziadowiec,
Adam Piasecki
et al.

Abstract: This research aimed to evaluate the material properties of reactive extrusion-modified blends containing PET multilayered foil waste. Three types of PET-based multilayer foil waste were used as the compound during the reprocessing of standard bottle-grade PET. Flakes used for this purpose were made from laminated foils: (A) PET/PE, (B) PET/EVOH/PE, and PET/PE/met. All types of the prepared materials were compounded with 30% of the waste foil flakes. Additionally, the blend was modified with an epoxy-based chai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 39 publications
1
2
0
Order By: Relevance
“…Meanwhile, for the elastomer-modified material PETG/(PET/MET)-IM, the T cc position moved to 138 °C. The same behavior was noticed for the other groups of materials, which confirmed that the observed phenomenon was directly connected with the presence of the POE-g-GMA phase [ 53 , 70 ]. Since this type of elastomer is functionalized by glycidyl methacrylate groups, strong interfacial interactions are likely formed between the polyester matrix and the elastomer inclusion [ 71 , 72 , 73 , 74 ].…”
Section: Resultssupporting
confidence: 82%
See 2 more Smart Citations
“…Meanwhile, for the elastomer-modified material PETG/(PET/MET)-IM, the T cc position moved to 138 °C. The same behavior was noticed for the other groups of materials, which confirmed that the observed phenomenon was directly connected with the presence of the POE-g-GMA phase [ 53 , 70 ]. Since this type of elastomer is functionalized by glycidyl methacrylate groups, strong interfacial interactions are likely formed between the polyester matrix and the elastomer inclusion [ 71 , 72 , 73 , 74 ].…”
Section: Resultssupporting
confidence: 82%
“…A natural suggestion for further work on this topic could be to optimize the composition of the developed blends, especially in terms of the impact modifier (IM) content. The constant content of 20% used during the tests was estimated in accordance with the guidelines of manufacturers of this type of additive, as well as previous research in this area, including our own [ 53 , 97 , 98 ]. The use of a smaller amount of the IM additive could maintain the higher stiffness/strength of the prepared blends; additionally, the reduced content of the relatively expensive elastomer would also be economically justified.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation